Pengaruh Pemberian Air Kelapa (Cocos nucifera. L) pada Media Agar Darah terhadap Pertumbuhan Bakteri Mycobacterium tuberculosis - Maria Nuraeni; Rosnita Sebayang (Jurnal Kesehatan, 2018)
Tuberculosis is still becoming a health problem in Indonesia. High prevalence of Tuberculosis has encouraged efforts so that patients get treatment immediately. The gold standard to diagnose the disease is by performing bacteriae culture. The culture media for Mycobacterium tuberculosis is quite expensive and also takes quite a long period to let the bacteriae grow up. A blood agar plate is a nonselective media enabling the growth almost all bacteriae. Hopefully, the growth of Mycobacterium tuberculosis becomes more rapid by providing coconut water on a blood agar plate. This study was to provide the effects of provision coconut water with the concentration 50%, 75% and 100% on blood agar plate which were incubated at temperature 35 C and 37 oC. This was an experimental study using pure strain  Mycobacterium tuberculosis (H37RV). The result of the study showed that Mycobacterium tuberculosis was able to grow up in a blood agar plate with coconut water 100% concentration which added to the media. Incubation time was 14 days at temperature 35°C and 37°C. Regression logistic test showed a significant value of the concentration, temperature, and duration variable were 0,738, 0,872 and 0,720, respectively. There was no effect of coconut water concentration, temperature dan incubation period to the growth of Mycobacterium tuberculosis.